Phase 2 study of sunitinib in patients with metastatic mucosal or acral melanoma. Issue 22 (11th August 2015) - Buchbinder, Elizabeth I.; Sosman, Jeffrey A.; Lawrence, Donald P.; McDermott, David F.; Ramaiya, Nikhil H.; Van den Abbeele, Annick D.; Linette, Gerald P.; Giobbie‐Hurder, Anita; Hodi, F. Stephen
Abstract : BACKGROUND: Patients with mucosal and acral melanomas have limited treatment options and a poor prognosis. Mutations of the KIT oncogene in these melanoma subtypes provide a potential therapeutic target. METHODS: A multicenter phase 2 trial of sunitinib was conducted in patients with unresectable stage III or IV melanoma of a mucosal or acral primary origin. Patients were treated in 2 cohorts: cohort A received sunitinib at a dose of 50 mg daily for 4 weeks of a 6‐week cycle, and cohort B received sunitinib at a dose of 37.5 mg daily on a continuous basis. Dose reductions were permitted for treatment‐related toxicities, and tumor assessments were performed every 2 months. RESULTS: Fifty‐two patients were enrolled: 21 in cohort A and 31 in cohort B. Four patients had confirmed partial responses, which lasted 5 to 10 months (1 with a KIT mutation). In both cohorts, the proportion of patients alive and progression‐free at 2 months was 52% (95% confidence interval, 38%‐66%); this was significantly larger than the hypothesized null of 5%. There was no significant difference in response or overall survival between the 25% of patients with a KIT mutation and those without one (response rate, 7.7% vs 9.7%; overall survival, 6.4 vs 8.6 months). The overall disease control rate was 44%, and a high rate of toxicity was associated with the treatment. CONCLUSIONS: Sunitinib showed activity in the treatment of mucosal and acral melanoma that was not dependent on the presence of a KIT mutation. However, the medication was poorly tolerated, and there were no prolonged responses. Cancer 2015;121:4007–4015. © 2015 American Cancer Society . Abstract : Sunitinib has activity in the treatment of mucosal and acral melanoma that is not dependent on the presence of a KIT mutation. However, the medication is poorly tolerated, and there are no prolonged responses.